Kajian Literatur Senyawa-Senyawa Anti Pada Protein Susu Kuda Terhadap Virus Dari Genus Flavivirus Dan Betacoronavirus - Elshada Here; Annytha I. R Detha; Diana A Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Milk contains carbohydrates (lactose), protein, fat, vitamins and minerals. Horse milk has a whey protein composition such as lactoferrin, lysozyme, beta-lactoglobulin, alpha-lactoalbumin, immunoglobulin (Ig) and Bovine Serum Albumin. This literature study was conducted to describe the mechanism of the ability of antiviral compounds that contained in horse milk protein against viruses fromb the genus Flavivirus, the mechanism of ability of antiviral compounds contained in horse milk proteins against viruses from the genus Betacoronavirus. The preparation of this literature study was carried out from August to October 2021 which included searching references or libraries that were closely related to the title of Google Scholar using the Mendeley application, resumes and writing literature studies related to the workings of the antiviral compounds present in milk protein. horse which can be a therapeutic agent for viral disease in animals of the genus Flavivirus. Based on the literature review of the antiviral compounds from horse milk protein studied, it can be concluded that lactoferrin inhibits Japanese encephalitis virus infection in host cells mediated by lobes and lobes. Lactoferrin inhibits the attachment of SARS-CoV-2 to the host cell membrane involving the interaction of Heparan sulfate proteoglycans (HSPGs) on the surface of the host cell membrane. An envelope (E) protein found on the surface of the dengue virus hermorrhagic fever (DBD) that involved in virus transfer in host cells then infecting host cells and can be hindered by the ability of lactoferrin to interfere with the virus ability to infect host cells by attach the the Heparan sulfate proteoglycans (HSPGs).